An Analysis of the Online Learning Experience and Its Effect on Stress in Management Students of SBM ITB Batch 2021 - Manuella, Lumban Tobing Amanda; Putranto, Nur Arief Rahmatsyah (Journal of Business and Management, 2021)
The Covid-19 pandemic has spread across the globe and is one of the reasons for limiting human activities, one of which is schooling. One of the nations impacted by the Covid-19 pandemic is Indonesia. The Indonesian Ministry of Education and Culture published a policy addressing teaching and learning activities for all levels of education, starting with early childhood education and ending with universities, which must take out online teaching and learning activities by March 2020. The use of online learning activities is definitely not simple since it is something new, and, of course, there are benefits and drawbacks as well as difficulties that emerge in its implementation. This research will look at the experiences of SBM ITB management students from the class of 2021 and how they affect student stress. The findings of this research were obtained via a qualitative method. Gadzella's Student-Life Stress Inventory was used in this study. In conclusion, there are three degrees of stress: mild, moderate, and severe. Mild stress is the most frequent. This study found that students only experienced mild to moderate stress. Interactions (frustration), academic load (pressure), the environment (changes) and infrastructure (frustration) are all stressors. Students' physiological and emotional reactions to stress are distinct. They experience backaches, aches, and tired eyes. They are lonely, mentally tired, bored, and depressed. The data analysis presented showed both positive and negative aspects of online learning. It reduces physical fatigue, improves understanding of the material, is more flexible, and costs less. Online learning has a negative psychological and physical effect on students. Keywords: Online Learning, Stress, Stressor